Development of Song Media Assisted with Canva To Improve the Acrostic Poetry Writing Skills - An-Nisa, Betha Centaury; Sutikno, Putri Yanuarita (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This research aims to improve students' skills in writing acrostic poetry through the development of canva-assisted song media, in the form of an audio visual entitled "Alam Asriku". One of the problems found during observations and interviews with grade V teachers at SDN 01 Balong, Karanganyar Regency is the low skill of writing acrostic poetry in the subject of Indonesian Language. Therefore, one of the alternatives to this problem is the use of the song media "Alam Asriku", which will facilitate and help students in their imagination to develop ideas and ideas, as well as increase vocabulary so that students can improve their skills in writing acrostic poetry. The subjects in this study are class V students totaling 20 students. The type of research used is the mix method. Qualitative is carried out by triangulation of data sources and quantitative by analyzing pre-test and post-test score data with SPSS. The significance value obtained from the paired sample t test was 0.000 and the N-Gain value obtained was 71.38%, indicating a high increase. Based on this, it can be concluded that the use of canva-assisted composition song media is effective and can improve students' acrostic poetry writing skills.